LITERATURE REVIEW : IMPLEMENTASI K3RS DI RUMAH SAKIT DI KOTA PADANG - Alfita Dewi; Ilma Nuria Sulrieni; Mohammad Farid; Friska Eka Fitria (Smart Education, 2026)
Abstract: Hospital Occupational Safety and Health (OSH) is a crucial aspect in ensuring the safety of healthcare workers, patients, and the hospital work environment. The implementation of OSH is a particular concern, particularly in hospitals in Padang City, which face high and complex occupational risks. This study aims to systematically examine the implementation of OSH in hospitals in Padang City through a literature review. The method used was a search of scientific articles from various databases such as Google Scholar, PubMed, and ScienceDirect, with the inclusion criteria being articles published within the last five years and relevant to the topic of OSH. The study results indicate that OSH implementation in hospitals in Padang City has been ongoing but is not yet optimal, characterized by limitations in policies, human resources, compliance with standard operating procedures, and a lack of training and supervision. Furthermore, safety culture and management commitment also influence the success of OSH implementation. The study concludes that improving OSH implementation requires strengthening internal regulations, improving workforce competency, and a sustained commitment from hospital management to create a safe and healthy work environment. Keywords: K3RS, Occupational Safety, Hospital, Implementation, Literature Review. Abstrak: Keselamatan dan Kesehatan Kerja Rumah Sakit (K3RS) merupakan salah satu aspek penting dalam menjamin keselamatan tenaga kesehatan, pasien, serta lingkungan kerja di rumah sakit. Implementasi K3RS menjadi perhatian khusus, terutama di rumah sakit di Kota Padang yang memiliki risiko kerja tinggi dan kompleks. Penelitian ini bertujuan untuk mengkaji secara sistematis implementasi K3RS di rumah sakit di Kota Padang melalui pendekatan literature review. Metode yang digunakan adalah penelusuran artikel ilmiah dari berbagai database seperti Google Scholar, PubMed, dan ScienceDirect dengan kriteria inklusi artikel yang diterbitkan dalam 5 tahun terakhir dan relevan dengan topik K3RS. Hasil kajian menunjukkan bahwa implementasi K3RS di rumah sakit di Kota Padang telah berjalan namun belum optimal, ditandai dengan masih adanya keterbatasan dalam kebijakan, sumber daya manusia, kepatuhan terhadap standar operasional prosedur, serta kurangnya pelatihan dan pengawasan. Selain itu, faktor budaya keselamatan dan komitmen manajemen juga berpengaruh terhadap keberhasilan implementasi K3RS. Kesimpulan dari studi ini adalah bahwa peningkatan implementasi K3RS memerlukan penguatan regulasi internal, peningkatan kompetensi tenaga kerja, serta komitmen berkelanjutan dari pihak manajemen rumah sakit guna menciptakan lingkungan kerja yang aman dan sehat. Kata Kunci: K3RS, Keselamatan Kerja, Rumah Sakit, Implementasi, Literature Review.